2016
DOI: 10.1109/tmag.2016.2577628
|View full text |Cite
|
Sign up to set email alerts
|

Current-Induced Pinwheel Oscillations in Perpendicular Magnetic Anisotropy Spin Valve Nanopillars

Abstract: Nanopillar spin valve devices are typically comprised of two ferromagnetic layers: a reference layer and a free layer whose magnetic orientation can be changed by both an external magnetic field and through the introduction of spin-polarized electric current. Here we report the continuous repeated switching behavior of both the reference and free layers of a perpendicular spin valve made of Co/Pd and Co/Ni multilayers that arises for sufficiently large DC currents. This periodic switching of the two layers pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…3(c). As determined experimentally and numerically in previous studies [15][16][17], the frequency increases with an increase of |J|. Note that the shape of spikes can also be tuned by controlling the switching time ratio through materials engineering of the two layers (M s , P etc.).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…3(c). As determined experimentally and numerically in previous studies [15][16][17], the frequency increases with an increase of |J|. Note that the shape of spikes can also be tuned by controlling the switching time ratio through materials engineering of the two layers (M s , P etc.).…”
Section: Resultsmentioning
confidence: 54%
“…It has been predicted, as well as experimentally observed that this torque configuration can generate a windmill-like motion of the two magnetizations [15][16][17]. The equations of motion of the magnetizations are given by the Landau-Lifschitz-Gilbert-Slonczewski (LLGS) equation [9,10,32] :…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Such behavior causes a second threshold in the write-voltage, above which additional write-error would occur. [14][15][16][17][18] To mitigate these issues, it is essential to fully understand the STT-related magnetic dynamics on both sides of the tunnel barrier in an p-MTJ.…”
Section: Introductionmentioning
confidence: 99%
“…Most STOs studied up to date are effectively zerodimensional (0D) because the spin current in these devices is applied to a nanometer-scale region of the ferromagnet. Examples of such oscillators include (i) nanopillar spin valves [22][23][24][25][26][27] and nanoscale magnetic tunnel junctions [12,[28][29][30][31], (ii) nanocontacts to magnetic films and multilayers [32][33][34][35][36][37][38][39] and planar nanoconstriction spin Hall oscillators (SHOs) [40][41][42]. It was recently demonstrated that effectively one-dimensional (1D) SHOs can be realized in ferromagnetic nanowires where several low frequency spin wave eigenmodes are simultaneously driven into large-amplitude auto-oscillations by pure spin Hall current uniformly applied to a micrometer-scale active region of the nanowire [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%